An innovative multi-gap clutch based on magneto-rheological fluids and electrodynamic effects: magnetic design and experimental characterization. (5th December 2016) - Rizzo, R
Abstract: In this paper an innovative multi-gap magnetorheological clutch is described. It is inspired by a device previously developed by the author's research group and contains a novel solution based on electrodynamic effects, capable to considerably improve the transmissible torque during the engagement phase. Since this (transient) phase is characterized by a non-zero angular speed between the two clutch shafts, the rotation of a permanent magnets system, used to excite the fluid, induces eddy currents on some conductive material strategically positioned in the device. As a consequence, an electromagnetic torque is produced which is added to the torque transmitted by the magnetorheological fluid only. Once the clutch is completely engaged and the relative speed between the two shafts is zero, the electrodynamic effects vanish and the device operates like a conventional magnetorheological clutch. The system is investigated and designed by means a 3D FEM model and the performance of the device is experimentally validated on a prototype.